Stock Exchange Listings, Firm Value, and Security Market Efficiency: The Impact of NASDAQ - Sanger, Gary C.; McConnell, John J. (Journal of Financial and Quantitative Analysis, 1986)
Gary C. Sanger, John J. McConnell, Stock Exchange Listings, Firm Value, and Security Market Efficiency: The Impact of NASDAQ, The Journal of Financial and Quantitative Analysis, Vol. 21, No. 1 (Mar., 1986), pp. 1-25